Mobile-Based Box Breathing Application Blood Pressure in Pregnant Women at Risk of Preeclampsia - Aprina Aprina; Titi Astuti; Anita Anita (Poltekkes Kemenkes Palu, 2025)
Background: Preeclampsia is a pregnancy-related hypertensive disorder that remains a major contributor to maternal and perinatal morbidity and mortality. Non-pharmacological interventions, such as box breathing, have gained attention as complementary strategies for blood pressure control in pregnant women at risk of preeclampsia. This study aimed to examine the effect of a mobile-based box breathing intervention on blood pressure among pregnant women at risk of preeclampsia. Methods: A pre-experimental study with a one-group pretest–posttest design was conducted among 197 pregnant women recruited using purposive sampling from four hospitals in Lampung Province, Indonesia. Blood pressure was measured before and after the intervention, and data were analyzed using a paired sample t-test. Results: The mean systolic blood pressure decreased from 139.46 mmHg (SD = 14.28; range 105–195 mmHg) to 122.93 mmHg (SD = 10.91; range 96–167 mmHg), with a mean difference of 16.53 mmHg (SD = 13.43; p < 0.001). The mean diastolic blood pressure declined from 90.15 mmHg (SD = 11.90; range 56–156 mmHg) to 82.46 mmHg (SD = 8.21; range 66–106 mmHg), with a mean difference of 7.69 mmHg (SD = 10.74; p < 0.001). Conclusion: Mobile-based box breathing was associated with a significant reduction in both systolic and diastolic blood pressure among pregnant women at risk of preeclampsia.